Employee well-being and job satisfaction in tourism: Insights from a systematic review and content analysis - Pınar Çelik; Nisa Ekşili; Andreas Papatheodorou (Journal of Tourism, Heritage & Services Marketing)
Purpose: This systematic literature review explores the relationship between employee well-being and job satisfaction within the tourism industry. The study aims to identify current knowledge, theoretical frameworks, research methodologies, and trends, while highlighting gaps and suggesting areas for future research within the service marketing triangle context. Methods: The researchers employed a systematic literature review and content analysis, examining 39 peer-reviewed articles sourced from the Web of Science database. Studies were evaluated based on their relevance to employee well- being and job satisfaction, categorizing them according to the service marketing triangle into employee-business, employee-customer, and business-customer interactions. Analysis techniques included bibliometric mapping using VOSviewer and manual content analysis with Microsoft Excel. Results: Findings indicate a notable growth in studies post-2018, predominantly focusing on internal organizational factors affecting employee well-being. Leadership styles, workplace culture, and organizational support emerged as critical variables. Conversely, research addressing external factors, such as employee-customer interactions and corporate social responsibility initiatives, remains limited. Implications: This review underscores the strategic importance of employee well-being for enhancing customer satisfaction and organizational performance. It recommends broadening research to include external service interactions and customer-facing roles, advocating holistic approaches to employee well-being in policy development and industry practice.